2012
DOI: 10.1007/s00425-012-1650-x
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid biosynthesis-related genes in grape skin are differentially regulated by temperature and light conditions

Abstract: Temperature and light are important environmental factors that affect flavonoid biosynthesis in grape berry skin. However, the interrelationships between temperature and light effects on flavonoid biosynthesis have not been fully elucidated at the molecular level. Here, we investigated the effects of temperature and light conditions on the biosynthesis of flavonoids (anthocyanins and flavonols) and the expression levels of related genes in an in vitro environmental experiment using detached grape berries. Suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
366
1
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 427 publications
(414 citation statements)
references
References 65 publications
43
366
1
4
Order By: Relevance
“…Treatment duration; however, tended to change C4H and CHS gene expression as their expression levels were consistent with total flavonoid content, further supporting the close relation between flavonoids biosynthesis and C4H and CHS expression. Similar results were reported in grape skin (V. labruscana) [7] and tomato plants (Solanum lycopersicum cv. Suzanne) [31] showing increased CHS expression in response to lower temperatures.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Treatment duration; however, tended to change C4H and CHS gene expression as their expression levels were consistent with total flavonoid content, further supporting the close relation between flavonoids biosynthesis and C4H and CHS expression. Similar results were reported in grape skin (V. labruscana) [7] and tomato plants (Solanum lycopersicum cv. Suzanne) [31] showing increased CHS expression in response to lower temperatures.…”
Section: Discussionsupporting
confidence: 88%
“…It has been clearly demonstrated that environmental factors, such as temperature, light, and soil moisture content, affect flavonoid biosynthesis and accumulation in many plants [4][5][6][7]. Additionally, several flavonoid biosynthesis pathway genes are expressed various parts of flowering plants (e.g., flowers, fruits, seeds, and leaves), with some have been isolated and characterized (e.g., grape [8]; azaleas [9,10]; bilberry [11,12]; Ginkgo [13]).…”
Section: Introductionmentioning
confidence: 99%
“…• C and anthocyanin concentrations were also decreased in grapes [24]. In light of the results of the present experiment, it appears that the range of temperature in the greenhouse was suitable for anthocyanin formation in apples.…”
Section: Temperature and Anthocyanin Formationsupporting
confidence: 56%
“…Also, Meng et al (2004) reported that the red colouration in ray floret of Gerbera hybrid is influenced and controlled by light. The low accumulation and composition of carotenoids and anthocyanin pigments in the overlapped part is due to the shading effect on the bracts (Cortell and Kennedy, 2006;Azuma et al, 2012). …”
Section: Discussion Pigment Analysis During Inflorescence Developmentmentioning
confidence: 99%
“…Cortell and Kennedy (2006) have reported the effects of shading on the accumulation of anthocyanins and flavonoids in the Vitis vinifera L. fruit. Several researchers have reviewed that the environmental stimuli like light and temperature play a key role in the regulation of anthocyanins and carotenoid synthesis pathway in the fruits and also flowers (Meng et Guo and Wang, 2010;Azuma et al, 2012). Alebidi (2013) similarly reported that shading severely suppressed anthocyanin accumulation in the Malaysian wax apple skin.…”
Section: Effects Of Shading Treatmentsmentioning
confidence: 99%